Biomarkers of Environmental Enteropathy are Positively Associated with Immune Responses to an Oral Cholera Vaccine in Bangladeshi Children. - Muhammad Ikhtear Uddin; Shahidul Islam; Naoshin S Nishat; Motaher Hossain; Tanzeem Ahmed Rafique; Rasheduzzaman Rashu; Mohammad Rubel Hoq; Yue Zhang; Amit Saha; Jason B Harris; Stephen B Calderwood; Taufiqur Rahman Bhuiyan; et al. (PLOS Neglected Tropical Diseases, 2016)
Environmental enteropathy (EE) is a poorly understood condition that refers to chronic alterations in intestinal permeability, absorption, and inflammation, which mainly affects young children in resource-limited settings. Recently, EE has been linked to suboptimal oral vaccine responses in children, although immunological mechanisms are poorly defined. The objective of this study was to determine host factors associated with immune responses to an oral cholera vaccine (OCV). We measured antibody and memory T cell immune responses to cholera antigens, micronutrient markers in blood, and EE markers in blood and stool from 40 Bangladeshi children aged 3-14 years who received two doses of OCV given 14 days apart. EE markers included stool myeloperoxidase (MPO) and alpha anti-trypsin (AAT), and plasma endotoxin core antibody (EndoCab), intestinal fatty acid binding protein (i-FABP), and soluble CD14 (sCD14). We used multiple linear regression analysis with LASSO regularization to identify host factors, including EE markers, micronutrient (nutritional) status, age, and HAZ score, predictive for each response of interest. We found stool MPO to be positively associated with IgG antibody responses to the B subunit of cholera toxin (P = 0.03) and IgA responses to LPS (P = 0.02); plasma sCD14 to be positively associated with LPS IgG responses (P = 0.07); plasma i-FABP to be positively associated with LPS IgG responses (P = 0.01) and with memory T cell responses specific to cholera toxin (P = 0.01); stool AAT to be negatively associated with IL-10 (regulatory) T cell responses specific to cholera toxin (P = 0.02), and plasma EndoCab to be negatively associated with cholera toxin-specific memory T cell responses (P = 0.02). In summary, in a cohort of children 3-14 years old, we demonstrated that the majority of biomarkers of environmental enteropathy were positively associated with immune responses after vaccination with an OCV.